2007
DOI: 10.2298/jsc0704407p
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of CO2 extraction of marigold (Calendula officinalis L.)

Abstract: Essential oil content (0.05 %) of marigold (Calendula officinalis L.) was determined using the official steam distillation procedure. High-pressure CO 2 extraction of plant material under supercritial (100, 200 and 300 bar and 40°C) and subcritical (60, 90 and 120 bar and 15°C) conditions for 3 h was investigated. It was found that the increase in the pressure promoted an increase in the yield. The essential oil contents obtained from the investigated CO 2 extracts by steam distillation were significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 13 publications
0
22
0
6
Order By: Relevance
“…The identified compounds are listed in Table 1. GS-MS analysis showed that sesquiterpenes and their derivatives were the main compounds in marigold extracts, but not the only one, such as that found in the marigold from Brazil [6] and Serbia [7]. The total amount of sesquiterpene hydrocarbons and sesquiterpenols was in the range 51.6-68.5%.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The identified compounds are listed in Table 1. GS-MS analysis showed that sesquiterpenes and their derivatives were the main compounds in marigold extracts, but not the only one, such as that found in the marigold from Brazil [6] and Serbia [7]. The total amount of sesquiterpene hydrocarbons and sesquiterpenols was in the range 51.6-68.5%.…”
Section: Resultsmentioning
confidence: 91%
“…The compounds were identified by comparison of their linear retention indices (LRI) relative to C 8 -C 24 n-alkanes obtained on a non-polar DB-5 column with those provided in the database [16] and by matching their mass spectra to the data in NIST 05 library and to the results reported elsewhere [6][7][8]10].…”
Section: Gas Chromatographic-mass Spectrometric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated therapeutic potentialities of Calendula officinalis L. such as anti-inflammatory activity [2][3][4][5], immunomodulatory [6][7], Hepatoprotective [8], wound-healing [9], antioxidant [10][11][12], antibacterial and antiparasitic activity [13][14][15][16]. The essential oil from C. officinalis has been also investigated [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%